Sugar transporter gene family: structure, evolution, and expression analysis in Beta vulgaris - Parviz Heidari; Mostafa Ahmadizadeh; Mohammadamin Hosseinzadeh (Vegetable Research)
Sugar transporters are key mediators of the distribution of photosynthesis products in plant organs and play a key role in maintaining the sugar balance in cells. In this study, for the first time, all sugar transporters in Beta vulgaris (BvSUTR) were identified and compared based on their structure and function. A total of 61 BvSUTR genes were identified, and they were classified into four subfamilies: sugar/inositol transporter, sucrose/H+ symporter, nucleotide-sugar transporter, and sweet sugar transporter. Gene structures and physiochemical characteristics varied significantly across the phylogenetic groups, with a lower prevalence of phosphorylation regions detected in individuals belonging to group I and group V, which are part of the sweet sugar transporter subfamily. Additionally, there was a variation in the number of transmembrane helices from 5 to 12, notably fewer in the sweet sugar transporter subfamily. Moreover, the BvSUTR proteins displayed distinct three-dimensional structures and binding sites, where serine and leucine residues were found to be more prevalent in the binding locations. Analysis of the upstream region revealed that cis-regulatory elements related to growth, light, and abscisic acid (ABA) responsiveness are repeated in the promoter region of BvSUTRs. The expression profile revealed that SUTRs are less expressed in response to abiotic stresses. Analysis of the interaction network revealed that there is a strong interaction between sugar transporters and members of this gene family, which further influences the function of their other paralogs. The results of this research can be used in molecular research related to sugar beet breeding programs.